Exercise-based priming in team sports: practical guidelines for enhancing neuromuscular readiness and reducing injury risk - Peña, J.; Colomar, J.; Piedra, A.; Vicens-Bordas, J.; Altarriba-Bartés, A. (Apunts Sports Medicine, 2025)
Exercise-based priming has emerged as a valuable pre-competition strategy to enhance neuromuscular readiness, acute physical performance, and potentially reduce injury risk in team sport athletes. While the scientific rationale for priming is increasingly well-documented, there remains a need to translate these findings into actionable frameworks. This article aims to provide staff members and practitioners with evidence-informed, practical guidelines for implementing priming protocols before the competition. The proposals are tailored to the intermittent and multidirectional nature of team sports, with a focus on enhancing key explosive actions such as sprinting, jumping, and changes of direction. Importantly, the guidelines consider factors such as timing, exercise selection, and intensity to support both performance optimization and the prevention of musculoskeletal injuries. By bridging scientific evidence with practical application, this paper facilitates the safe and effective integration of priming strategies into pre-competition routines within team sport environments.